ANALISIS INDEKS MASSA TUBUH (IMT) ATLET BOLA BOLI TUNAS PANATAYUDHA USIA 16-18 TAHUN - Fauzi Shaputra Husin; Ilaika Al Quratu Aini; Moh. Supriyadi; Habibi Hadi Wijaya; Iha Nursolihah; Maha Dewi Afifah Nurhadi (Universitas Ngudi Waluyo, 2024)
Body Mass Index (BMI) is a common measure used to assess a person's nutritional status. In sports such as volleyball, BMI is an important factor in supporting the game. This study aims to analyze the nutritional status of adolescent volleyball athletes. This study used an observational approach involving 50 adolescent volleyball athletes from various clubs. The nutritional status of children aged 16-18 years can be known based on the results of anthropometric measurements of Body Weight (BB) and Height (TB) according to age (TB/A), and Body Mass Index according to age (BMI/A). Data were analyzed descriptively using SPSS. The results of the analysis showed that there were 35 (70%) athletes with a normal nutritional status category and 15 (30%) athletes with an obese nutritional status. The conclusion of this study is that most athletes have normal nutritional status, but there are still athletes with obese nutritional status Abstrak Indeks Massa Tubuh (IMT) adalah ukuran umum yang digunakan untuk menilai status gizi seseorang. Dalam olahraga seperti bola voli, IMT merupakan faktor penting dalam menunjang permainan. Penelitian ini bertujuan untuk menganalisis status gizi atlet bola voli remaja. Penelitian ini menggunakan pendekatan observasional dengan melibatkan 50 atlet bola voli remaja dari berbagai klub. Status gizi anak umur 16-18 tahun dapat diketahui dengan berdasarkan hasil pengukuran antopometri Berat Badan (BB) dan Tinggi Badan (TB) menurut umur (TB/U), dan Indeks Massa Tubuh menurut umur (IMT/U). Data dianalisis secara deskriptif menggunakan SPSS. Hasil analisis menunjukkan bahwa terdapat atlet dengan kategori status gizi normal sebanyak 35 (70%) orang dan kategori gemuk sebanyak 15 (30%) orang. Kesimpulan dari penelitian ini adalah sebagian besar atlet memiliki status gizi normal, akan tetapi masih terdapat atlet dengan status gizi gemuk